1992
DOI: 10.1093/intimm/4.10.1113
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency of endogenous antigen presentation by MHC class II molecules

Abstract: MHC class II molecules are involved in the presentation of both exogenous and endogenous antigens to CD4 T cells. Using the trans-membrane hemagglutinin (HA) from measles virus and the secreted hen egg lysozyme (HEL) as antigen models, we have compared the efficiency of MHC class II presentation by naive antigen presenting cells (APCs) pulsed with exogenous antigen with that of their transfected counterparts synthesizing endogenous antigen. B cells expressing even a very low amount of trans-membrane HA were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 0 publications
2
22
0
1
Order By: Relevance
“…MHC class II presentation of endogenous secreted hen egg lysozyme was much more efficient when compared with that of exogenous hen egg lysozyme and was not explained by reuptake of secreted antigen. 20 Rowell et al 21 demonstrated that class II presentation of the HIV-1 envelope protein by infected antigen-presenting cells may be mediated by rapid endocytosis from the cell surface, but also that class II MHC presentation occurred under conditions that prevented reuptake by endocytosis, indicating that an internal pathway for class II presentation exists. The in vivo data in the present investigation indicate that expression by antigen-presenting cells of secreted and circulating antigens potentiates humoral immune responses and is likely to be useful for efficient vaccination against such antigens.…”
Section: Discussionmentioning
confidence: 99%
“…MHC class II presentation of endogenous secreted hen egg lysozyme was much more efficient when compared with that of exogenous hen egg lysozyme and was not explained by reuptake of secreted antigen. 20 Rowell et al 21 demonstrated that class II presentation of the HIV-1 envelope protein by infected antigen-presenting cells may be mediated by rapid endocytosis from the cell surface, but also that class II MHC presentation occurred under conditions that prevented reuptake by endocytosis, indicating that an internal pathway for class II presentation exists. The in vivo data in the present investigation indicate that expression by antigen-presenting cells of secreted and circulating antigens potentiates humoral immune responses and is likely to be useful for efficient vaccination against such antigens.…”
Section: Discussionmentioning
confidence: 99%
“…7C) or if the distribution of specificity was based on the known access of proteins to MHC class II (Fig. 7D), where we estimated a fivefold advantage in access to class II molecules for the membrane proteins HA and NA, which is almost certainly an underestimate (10,12,13,67,84). One can see from this analysis that although the primary CD4 response has T cells specific for peptides contained in all the viral proteins tested, NS1 appears to be the most "immunogenic" relative to its size.…”
Section: T-cell Specificity To Influenza Virus Infection 6567mentioning
confidence: 94%
“…10). However, although there is evidence for activation of CD4 ϩ T cells by DNA-encoded proteins (9,11,12, reviewed in Ref. 13), epitopes of endogenous proteins expressed in the cytoplasm of transfected cells are commonly presented by MHC class I molecules to cytotoxic CD8 ϩ T-cells.…”
Section: Mhc 1 Ii-directed Antigen Activation Of Cd4 ϩ T-cells Is Vitmentioning
confidence: 99%